Al-Manhaj Al-Muqtarah Lita’lÎmillughah Al-‘Arabiyyah Lil Madâris Al-I’dâdiyyah Al-Islâmiyyah Al-Mukatsafah Bi Indûnîsiya - Khaulah Ishomuddin (Universitas Muhammadiyah Yogyakarta, 2021)
The objective of this research is to design a proposed curriculum of Arabic teaching for Integrated Islamic Junior High School (SMPIT) in Indonesia. This research was conducted in SMPIT Al-Muchtar Bekasi, West Java. Meanwhile, the method employed in this research is descriptive qualitative analysis with data collection through observation, interviews, documentation, and field notes. The outcomes of this research entailed: 1) Lack of subject content, 2) Variation of teaching methods, 3) Lack of Arabic language coercion on students, 4) Weaknesses of students in Arabic grammatical learning.